Perbedaan Kecemasan Mahasiswa Universitas Negeri Malang yang Menyusun Skripsi Ditinjau dari Pola Asuh Orang Tua - Tajwidatul Hijaziyah; Nur Eva; Farah Tantiani (Flourishing Journal, 2021)
This research aimed to figure out about anxiety differences of students viewed from their parental styles. In addition, this research is also aimed to describe anxiety level of students of Universitas Negeri Malang who compile their thesis viewed from their parental styles. By alpha Cronbach reliability test, anxiety scale got p equal 0,885 and parental styles scale got p equal 0,956, which is p bigger than 0,05 it means that the instruments was appropriate for use. The analysis employed was descriptive and comparative with one-way anova analyzes. Descriptive analyze resulted from 119 subjects shows that 11 students (9.24 percent) have very high anxiety level; 41 students (34.25 percent) at high level; 28 students (25.53 percent) at mid-level; 33 students (23.53 percent) at low level and 6 students (5.04 percent) at very low level. The comparative analysis results with One-way anova obtain a significance value of 0.000 (p less than 0.05). It means there are anxiety differences of students in universitas negeri Malang who compiled thesis viewed from their parental styles. The analysis results generate conclusion that there are anxiety differences of students in universitas negeri Malang who compiled thesis viewed from their parental styles. Students who endured permissive and authoritarian parental styles from their parents have higher degree of anxiety compared to the democratic one while they are working on their thesis. Further researchers are recommended to apply qualitative approach to find more correlations between parental styles and anxiety holistically. Penelitian ini bertujuan untuk mengetahui perbedaan kecemasan yang ditinjau dari pola asuh orang tua pada mahasiswa. Selain itu penelitian ini juga untuk menggambarkan tingkat kecemasan mahasisswa yang menyusun skripsi di universitas negeri malang ditinjau dari pola asuh. Berdasarkan uji reliabilitas alpha cronbach didapatkan nilai p dari skala kecemasan 0,885 dan skala pola asuh orang tua 0,956, dimana p lebih besar dari 0,05 yang berarti skala tersebut layak digunakan. Penelitian kuantitatif berjenis deskriptif komparatif dengan analisis varians satu jalur (one-way anova). Hasil analisis deskriptif menunjukkan kecemasan kategori sangat tinggi sebanyak 11 orang (9,24 persen), kategori tinggi 41 orang (34,25 persen), kategori cukup 28 orang (25,53 persen), kategori rendah 33 orang (23,53) dan kategori sangat rendah 6 orang (5,04 persen). Analisis varian satu jalur menunjukkan nilai p sama dengan 0,000 kurang dari 0,05, yang berarti terdapat perbedaan kecemasan pada mahasiswa yang menyusun skripsi yang menerima pola asuh permisif, otoriter dan demokratis. Berdasarkan hasil analisis diperoleh kesimpulan yaitu terdapat perbedaan kecemasan pada mahasiswa yang menyusun skripsi apabila ditinjau dari pola asuh orang tua. Mahasiswa yang menerima pola asuh permisif dan otoriter memiliki kecemasan yang lebih tinggi selama proses menyusun skripsi daripada mahasiswa yang menerima pola asuh demokratis. Saran untuk peneliti selanjutnya diharapkan agar dapat melakukan penelitian dengan metode kualitatif sehingga dapat menggali informasi tentang keterkaitan pola asuh dan kecemasan lebih mendalam dan menyeluruh.